Pengaruh Panjang Serat dan Fraksi Volume Komposit Lidah Mertua Terhadap Pengujian Tarik - Husman, Husman; Armin, Andre Hasnuryadi; Yuliyanto, Yuliyanto (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
Technology is currently experiencing rapid development, especially in the field of industrial engineering materials. One of the advances in industrial engineering materials is the use of ornamental plants as materials for making composites. Natural fiber reinforced composites are the right choice to be used as composite materials. The aim of the research is to obtain the highest tensile test values at fiber lengths of 60 mm, 80 mm, 100 mm and fiber volume fractions of 10%, 20%, 30% with 6% NaOH alkaline treatment for 1 hour and heating at 80? for 2 hours. The method used is full factorial. Samples were made using the hand lay-up method. The influence of fiber length and fiber volume fraction on tensile testing is very large. The longer the fiber used, the greater the tensile strength. Likewise with the percentage of fiber, the more it is, the stronger it is. The highest tensile strength was 39.03 Mpa at a fiber length of 100 mm and a volume fraction of 30%. Meanwhile, the lowest tensile strength result was 15.07 MPa at a fiber length of 60 mm and a fiber volume fraction of 10%. From the test results, the tongue-in-law composite can be used to make helmets, because its tensile strength value is higher than the tensile strength of SNI helmet material which is only 33.93 MPa.